2014
DOI: 10.1039/c4ra01346h
|View full text |Cite
|
Sign up to set email alerts
|

A simple and eco-sustainable method for the sulfonylation of amines under microwave-assisted solvent-free conditions

Abstract: A new environmentally benign, simple, and efficient protocol for the sulfonylation of amines using microwave irradiation under solvent- & catalyst-free conditions is reported. The corresponding sulfonamides were obtained in excellent yields within short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Many catalysts are used for the synthesis of sulfonamides such as, β-Cyclodextrin 27 , water 28,29 , pyridine 30 , PPh 3 31 , DMAP 32 , CsF-Celite 33 , ZnO-nanoparticles 34 , MgO 35 . Lakroutet al, 36 have prepared somesulfonamide derivatives by sulfonylation of primary, secondary sulfonyl chlorides, amino acid esters and phenols under solvent-free microwave irradiation techniques. Pan et al, 28 synthesized a fewsulfonamides via I 2 -mediated reaction of sodium sulfinates with amines in an aqueous medium at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Many catalysts are used for the synthesis of sulfonamides such as, β-Cyclodextrin 27 , water 28,29 , pyridine 30 , PPh 3 31 , DMAP 32 , CsF-Celite 33 , ZnO-nanoparticles 34 , MgO 35 . Lakroutet al, 36 have prepared somesulfonamide derivatives by sulfonylation of primary, secondary sulfonyl chlorides, amino acid esters and phenols under solvent-free microwave irradiation techniques. Pan et al, 28 synthesized a fewsulfonamides via I 2 -mediated reaction of sodium sulfinates with amines in an aqueous medium at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Classically substituted sulfonamides may be formed from amines and sulfonyl chlorides, 9 by direct alkylation of sulfonamides with alkyl halides, 10 or through reductive amination. 11 The Mitsunobu reaction has also been employed to convert an alcohol into a sulfonamide.…”
mentioning
confidence: 99%
“…It was allowed to dry at ambient temperature. The mechanistic design for this reaction was in line with the view of Lakrout et al, [11] Stage1 in the mechanism shown above (Figure 1) depicts the action of tosyl chloride on 2-aminopyridine. The amine group in 2-aminopyridine attacks the sulphonyl group with the pi bond electron between sulphur and oxygen moving to oxygen.…”
Section: Complexation Of Methyl-n-(pyridin-2-yl)benzenementioning
confidence: 55%
“…The important IR spectral bands of the ligand and its metal complexes were given in Table 4. The ligand contains three potential donor sites: the heterocyclic nitrogen of azomethine, the oxygen of sulphonamide and the nitrogen of sulphonamide [11,24,25]. The IR frequency band of the ligand at 3734.13 cm − 1 was assigned to nitrogen of the sulphonamide, the band at 1249.91 cm − 1 was assigned to the sulphonamide oxygen and the band at 1681.98 cm − 1 was assigned to the heterocyclic azomethine nitrogen [19].…”
Section: Electronic Analysis Of Ligand and Complexesmentioning
confidence: 99%